Testicular Cancer Presenting as Gastric Variceal Hemorrhage - Carlos Eduardo Salazar-Mejía; David Hernández-Barajas; Edio Llerena-Hernández; José Luis González-Vela; María Inés Contreras-Salcido; Adriana González-Gutiérrez; Omar David Borjas-Almaguer; Luis Alberto Pérez-Arredondo; Blanca Otilia Wimer-Castillo (Case Reports in Gastrointestinal Medicine)
Testicular cancer is the most common solid malignancy affecting males between the ages of 15 and 35. The symptomatology caused by this tumor varies according to the site of metastasis. We present the case of a 26-year-old male who arrived to the emergency department with hematemesis. He had no previous medical history. On arrival, we noted enlargement of the left scrotal sac. There was also a mass in the left scrotum which provoked displacement of the penis and right testis. The serum alpha-fetoprotein level was 17,090 ng/mL, lactate dehydrogenase was 1480 U/L, and human chorionic gonadotropin was 287.4 IU/mL. Upper endoscopy revealed a type 1 isolated gastric varix, treated with cyanoacrylate. A CT scan showed extrinsic compression of the portal vein by lymphadenopathy along with splenic vein partial thrombosis, which caused left-sided portal hypertension. Neoadjuvant chemotherapy was started with etoposide and cisplatin, and seven days later the patient underwent left radical orchiectomy. A postoperative biopsy revealed a pure testicular teratoma. Noncirrhotic left portal hypertension with bleeding from an isolated gastric varix secondary to metastasic testicular cancer has not been described before. Clinicians must consider the possibility of malignancy in the differential diagnosis of a young man presenting with unexplained gastrointestinal bleeding.